Has the COVID-19 pandemic cooled down or stimulated the countertendencies of capital? A critical review - Leonardo Carnut; Lucas Uback; Áquilas Mendes (Economies, 2023)
This is a critical review of what the Marxist scientific literature presents on the forms of countertendency to falling profit rates carried out during the COVID-19 pandemic. The 33 articles included in this review were studied using a Marxist approach. The following elements of the articles were synthesized and criticized: the analysis matrices, the methodological aspects of the articles, the elements contrary to the law of the tendency of the rate of profit to fall, and the cases studied and their contexts of analysis. The articles reviewed allow us to state that during the COVID-19 pandemic, there was intensification in the forms of an increased degree of labour exploitation, cheapening of the elements of constant capital, and increased relative overpopulation and shareholder capital.
Keywords: 330; coronavirus; criticism; capitalism; review